Comparison of Two-Dimensional Shear Wave Elastography with Nine Serum Fibrosis Indices to Assess Liver Fibrosis in Patients with Chronic Hepatitis B: A Prospective Cohort Study - Liu, Jianxue; Li, Yafeng; Yang, Xueliang; Ji, Yonghao; Zhang, Yaoren; Wan, Qinyun; Dun, Guoliang; Lin, Shumei (Ultraschall in der Medizin - European Journal of Ultrasound, 2019)
Purpose To prospectively assess liver fibrosis with two-dimensional shear wave elastography (2D-SWE) in patients with chronic hepatitis B (CHB) and to compare the performance of this modality with that of serum indices using Scheuer scoring from liver biopsies as the reference standard.Materials and Methods 123 patients with CHB underwent 2D-SWE measurements and serological tests between April 2016 and February 2018. The 2D-SWE and serum indices in the diagnosis of liver fibrosis were assessed using receiver operating characteristic (ROC) analyses.Results The areas under ROC (AUCs) for 2D-SWE, aspartate transaminase-to-platelet ratio index, fibrosis index based on the four factors, Forns score, King’s score, FibroIndex, red cell distribution width-to-platelet ratio, Hepascore, type IV collagen, and hyaluronic acid were 0.851, 0.738, 0.701, 0.739, 0.734, 0.711, 0.692, 0.601, 0.640, and 0.522, respectively, in the diagnosis of substantial fibrosis, 0.975, 0.819, 0.792, 0.829, 0.818, 0.807, 0.732, 0.572, 0.676, and 0.544, respectively, in the diagnosis of severe fibrosis, and 0.972, 0.883, 0.862, 0.908, 0.889, 0.918, 0.808, 0.601, 0.807, and 0.775, respectively, in the diagnosis of cirrhosis. The AUCs of 2D-SWE in the diagnosis of substantial fibrosis, severe fibrosis, and cirrhosis were significantly higher than those of the serum indices (p < 0.05).Conclusion 2D-SWE is a reliable noninvasive method for the assessment of liver fibrosis in patients with CHB with better diagnostic performance than that of nine serum fibrosis indices.
Keywords: elasticity imaging techniques; liver cirrhosis; serum markers; image-guided biopsy; hepatitis B